Efforts to Improve the Quality of Al-Qur'an Reading and Writing Learning in Al-Wathoniyah Al-Islamiyah Sumenep Al-Qur'an Education Park (TPQ) - Nurul Hidayah; Fayruzah El-Faradis (Indonesian Journal of Advanced Research, 2023)
This study aims to find out how to improve the quality of learning to read and write Al-Qu'an in Al-Wathoniyah Al-Islamiyah Sumenep Al-Qur'an Education Park (TPQ). To find out more about the efforts made, the researchers used a descriptive qualitative research type. The method used is the method of interviews, observation and documentation. Based on the research results, it can be seen that the efforts made in improving the quality of learning to read and write the Koran at TPQ Al-Wathoniyah Al-Islamiyah Sumenep are (1) adding mufrodat material, (2) using a new method, namely the Ummi method, (3) ) teachers participate in training, and (4) there is an evaluation meeting. The supporting factors in improving the quality of learning to read and write the Koran at TPQ Al-Wathoniyah Al-Islamiyah are internal factors, namely the existence of student motivation in learning. While the external factors are: the methods used, learning media, reward and punishment, teachers, and the most important are parents. While the inhibiting factor is friends.